Coordination‐Induced Band Gap Reduction in a Metal–Organic Framework. Issue 8 (5th January 2022) - Peeples, Craig A.; Çetinkaya, Ahmet; Tholen, Patrik; Schmitt, Franz‐Josef; Zorlu, Yunus; Bin Yu, Kai; Yazaydin, Ozgur; Beckmann, Jens; Hanna, Gabriel; Yücesan, Gündoğ
Abstract: Herein, we report on the synthesis of a microporous, three‐dimensional phosphonate metal–organic framework (MOF) with the composition Cu3 (H5 ‐MTPPA)2  ⋅ 2 NMP (H8 ‐MTPPA=methane tetra‐ p ‐phenylphosphonic acid and NMP=N‐methyl‐2‐pyrrolidone). This MOF, termed TUB1, has a unique one‐dimensional inorganic building unit composed of square planar and distorted trigonal bipyramidal copper atoms. It possesses a (calculated) BET surface area of 766.2 m 2 /g after removal of the solvents from the voids. The Tauc plot for TUB1 yields indirect and direct band gaps of 2.4 eV and 2.7 eV, respectively. DFT calculations reveal the existence of two spin‐dependent gaps of 2.60 eV and 0.48 eV for the alpha and beta spins, respectively, with the lowest unoccupied crystal orbital for both gaps predominantly residing on the square planar copper atoms. The projected density of states suggests that the presence of the square planar copper atoms reduces the overall band gap of TUB1, as the beta‐gap for the trigonal bipyramidal copper atoms is 3.72 eV. Abstract : Coordination‐induced band gap reduction . Experimental Tauc plots indicate that TUB1 possesses indirect and direct band gaps of 2.4 eV and 2.7 eV, respectively. DFT calculations reveal two spin‐dependent gaps of 2.60 eV and 0.48 eV for the alpha and beta spins, respectively, with the lowest unoccupied crystal orbital for both gaps predominantly residing on the square planar copper atoms. This results in a lower overall band gap, as the beta‐gap for the trigonal bipyramidal copper atoms is 3.72 eV.